Genome-wide gene expression regulation as a function of genotype and age in C. elegans - Viñuela, Ana; Snoek, L. Basten; Riksen, Joost A.G.; Kammenga, Jan E. (Genome Research, 2010)
Gene expression becomes more variable with age, and it is widely assumed that this is due to a decrease in expression regulation. But currently there is no understanding how gene expression regulatory patterns progress with age. Here we explored genome-wide gene expression variation and regulatory loci (eQTL) in a population of developing and aging C. elegans recombinant inbred worms. We found almost 900 genes with an eQTL, of which almost half were found to have a genotype-by-age effect (gxaeQTL). The total number of eQTL decreased with age, whereas the variation in expression increased. In developing worms, the number of genes with increased expression variation (1282) was similar to the ones with decreased expression variation (1328). In aging worms, the number of genes with increased variation (1772) was nearly five times higher than the number of genes with a decreased expression variation (373). The number of cis-acting eQTL in juveniles decreased by almost 50% in old worms, whereas the number of trans-acting loci decreased by ∼27%, indicating that cis-regulation becomes relatively less frequent than trans-regulation in aging worms. Of the 373 genes with decreased expression level variation in aging worms, ∼39% had an eQTL compared with ∼14% in developing worms. gxaeQTL were found for ∼21% of these genes in aging worms compared with only ∼6% in developing worms. We highlight three examples of linkages: in young worms (pgp-6), in old worms (daf-16), and throughout life (lips-16). Our findings demonstrate that eQTL patterns are strongly affected by age, and suggest that gene network integrity declines with age.